A novel approach to identification and excision of a persistent sinus tract following a rectus fascial sling: A case report - William.D. Winkelman; Jacques.P. Sasson; Eman Elkadry (Elsevier, 2021)
Background: While Gore-Tex® sutures have excellent handling and cause minimal fibroblast activity and a less inflammatory response compared with other materials, they carry a risk of persistent sinus tract formation. Case: A patient underwent an autologous rectus fascial sling using Gore-Tex® and we describe a novel technique for identification and excision of the sinus tract. Conclusion: Preoperative imaging and staining of the sinus tract with methylene blue can aid in successful identification of the tract during surgery and may improve rates of successful treatment.